Prevalence and Risk Factors of Chronic Eczema in Urban and Rural Populations (Eastern Medical College Journal, 2025)
Background: Eczema affects around 10% of children in Western countries and has become much more common in ‘developing’ countries in recent years. Numerous factors have been identified as contributing to the rising prevalence of eczema and other atopic diseases. It has been proposed by the hygiene hypothesis that eczema occurs more frequently in urban areas than in rural ones. Therefore, we studied the prevalence and risk factors of chronic eczema among the adult population living in urban and rural areas.Materials and Methods: This was a retrospective observational study conducted in the Department of Dermatology, Eastern Medical College Hospital, Cumilla, Bangladesh during the period from July 2023 to June 2024. In this study, we included 100 suspected patients of chronic eczema attending the dermatology department coming from urban and rural areas.Results: Most of our study patients (61%) were female followed by male (39%). The mean age was 46.32±14.02 & 44.32±16.02 years in urban & rural groups respectively. The most common symptom was an itchy rash reported by 62% & 44% of urban & rural patients respectively. The prevalence of eczema was 68% & 56% and chronic eczema was found in 24% & 18% of urban & rural groups respectively. Family history (80.43% vs 78.38%), antibiotics used more than 3 times per day (50% vs 56.76%), and environmental factors (54.35% & 43.24%) were the most common risk factors among our urban & rural populations respectively.Conclusion: This study shows that the prevalence of chronic eczema appears to vary significantly between urban and rural populations, influenced by environmental, genetic, and lifestyle factors.Eastern Med Coll J. July 2025; 10 (1): 65-70